First description of the metopiine genus Trieces Townes, 1946 (Hymenoptera: Ichneumonidae) from the Indomalayan region with three new species from India - Ranjith, A.P.; Priyadarsanan, Dharma Rajan (European Journal of Taxonomy, 2022)
Trieces Townes, 1946 is one of the largest metopiine genera for which species have been described from all zoogeographical regions except the Indomalayan. The present study reports a major range extension of Trieces with the description of three new species from India. The described species are members of the onitis species group. An identification key to the Palearctic and Indomalayan species of the onitis group is included with the revised generic diagnosis and a key to separate Trieces from its closest genus Chorinaeus. Distribution pattern and character plasticity of Trieces are also discussed.